Nutrient and metal analyses of Chinese herbal products marketed for veterinary use. Issue 2 (31st January 2012) - Shmalberg, J.; Hill, R. C.; Scott, K. C.
Summary: Many Chinese herbs and herbal mixtures are fed to domestic animals for their reputed medicinal properties. These herbs could contribute to the intake of essential nutrients and toxic metals, but their composition is mostly unknown. The purpose of this study was to measure major nutrient (crude protein, crude fat, carbohydrate, fibre) and mineral (Ca, P, Mg, K, Na, Fe, Zn, Cu, Mn, Mo, S, Al, Cd, Ni, Pb) concentrations in samples of fourteen combination formulas labelled for veterinary use and commonly administered to horses and dogs. Three single herbs, Bupleurum chinense, Curcuma zedoaria and Astragalus membranaceus, each obtained from several sources, and Yunnan Baiyao, a proprietary hemostatic mixture, were also analysed. Proximate analyses and some mineral concentrations differed (p < 0.05) among single herbs, and high concentrations of several minerals were detected in some herbal combinations. Those containing the highest concentrations [g/kg dry matter (DM)] of calcium (92.4), iron (2.6) and manganese (0.28) could provide >38%, 142% and 96%, respectively, of recommended allowances in adult dogs, and >13%, 122% and 2%, respectively, of maintenance requirements in horses, at the maximum labelled dose assuming complete availability. Concentrations of cadmium, nickel and lead were below published oral tolerance levels. Aluminium concentrations (median 380, maximum 920 mg/kg DM) were higher than has been previously reported in Chinese herbs. These nutrient analyses suggest that herbal combinations marketed to veterinarians, when fed at the maximal labelled dose, are unlikely to produce clinically relevant changes in the dietary intake of essential nutrients. However, small amounts of non‐essential contaminant minerals are present in some formulas, and further research is necessary to understand the significance of this finding.